Comparative analysis of image enhancement techniques applied to CT liver image - Rela, Munipraveena; Nagaraja Rao, S (International Journal of Engineering and Technology, 2018)
Computed Tomography (CT) is very much useful for doctors to analyze biological changes of internal organs. CT images of liver and lungs will have low contrast. So doctors cannot identify all types of diseases from CT images. Hence image processing techniques are used to enhance the CT images to help doctors for diagnosis has considerable interests now a day. In this paper, different methods of image enhancement for low contract liver CT images are studied.Â Â
Keywords: CT Scan; Image Enhancement; Image Negative and Image Sharpening